(untitled) (Journal of Parents and Teachers, 2026)
Cristo Rey School runs a programme for pupils with special educational needs, Down’s syndrome or autistic traits. This pioneering initiative combines individualised support with participation in mainstream classes. Furthermore, it prioritises inclusion over academic achievement.